Child Marriage, Education, and Agency in Uganda. Issue 1 (2nd January 2016) - Wodon, Quentin; Nguyen, Minh Cong; Tsimpo, Clarence
ABSTRACT: This contribution relies on four different approaches and data sources to assess and discuss the impact of child marriage on secondary school enrollment and completion in Uganda. The four data sources are: (1) qualitative evidence on differences in community and parental preferences for the education of boys and girls and on the higher likelihood of girls to drop out of school in comparison to boys; (2) reasons declared by parents as to why their children have dropped out of school; (3) reasons declared by secondary school principals as to why students drop out; and (4) econometric estimation of the impact of child marriage on secondary school enrollment and completion. Together, the four approaches provide strong evidence that child marriage reduces secondary school enrollment and completion for girls with substantial implications for agency.